Inside Back Cover: Polyoxometalate‐Mediated One‐Pot Synthesis of Pd Nanocrystals with Controlled Morphologies for Efficient Chemical and Electrochemical Catalysis (Chem. Eur. J. 14/2015). Issue 14 (18th March 2015) - Kim, Dongheun; Seog, Ji Hyun; Kim, Minjune; Yang, MinHo; Gillette, Eleanor; Lee, Sang Bok; Han, Sang Woo
<x xml:space="preserve">Abstract</x> Single‐crystalline Pd nanocrystals (NCs) with controlled morphologies can be prepared by a polyoxometalate (POM)‐mediated one‐pot aqueous synthesis method. The POMs function as both reducing and stabilizing agents in the formation of NCs, and thus give a fine control over the nucleation/growth kinetics of NCs. The prepared NCs have excellent catalytic properties for electrochemical and chemical reactions, showing that the POMs play a pivotal role in determining the catalytic performance, as well as the growth, of NCs. For more details, see the Full Paper by S. B. Lee, S. W. Han et al. on page 5387 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>